Ethical dilemmas in the care of patients suffering from psychotic catatonia: a case report - Saccaro, Luigi F.; Privé, Barbara; D’Imperio, Ambra; Bridel, Claire; Sentissi, Othman; Wullschleger, Alexandre (Frontiers in Psychiatry, 2025)
BackgroundCoercive measures in psychiatric practice are controversial due to their potential for severe negative effects. Ethical debates focus on respecting autonomy, minimizing damaging effects, and acting in the patient’s best interest.CaseWe present a unique case of a young patient suffering from a first episode of catatonic psychosis, in which striking this balance was especially difficult given the patient’s complete mutism and opposition, given the absence of immediate danger to herself or others, the lack of anamnestic information, and her avoidance of social support, which would have meant that she would not have encountered psychiatric care, were it not for an exceptional government plan in place at the time of hospitalization. The patient showed a very favorable, persistent response to nonvoluntary treatment with haloperidol and lorazepam, which could be discussed and debriefed once she recovered, after almost 5 months of hospitalization and follow-up.DiscussionArguments for and against nonvoluntary treatment are reviewed based on discussion with the local ethics committee, providing a useful reference for future similar cases. Finally, this case highlights an atypical onset of psychosis in a previously high-functioning individual and explores the mental health impact of international tensions, particularly the Russian-Ukrainian war, on individuals.